CLINICAL PROFILE AND INCIDENCE OF INFECTION IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS AT MEDICAL INPATIENT INSTALLATION, DEPARTMENT OF INTERNAL MEDICINE, DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA IN 2016 - Desy Trilistyoati; Betty Agustina; Awalia Awalia (Universitas Airlangga, Surabaya, Indonesia, 2021)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease with unknown aetiology. SLE attacks multiple organs with diverse clinical manifestations. Most patients get immunosuppressant therapy that suppresses immune system, causing the body to be susceptible to infection. Objective: to describe clinical manifestations, laboratory abnormalities, and incidence of infections in SLE patients hospitalized at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia in 2016. Materials and Methods: Cross-sectional descriptive observational study used medical records of 273 SLE patients hospitalized at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia in 2016. Results: Clinical manifestations found in this study were malar rash 7.33%, discoid rash 2.93%, oral ulcer 8.42%, allopecia 16.48%, arthritis 26.74%, serositis 13.19%, kidney 35.9%, neurology 24.91%, anemia 73.71%, leucopenia 32.67%, lymphopenia 76.89%, and thrombocytopenia 33.86%. Laboratory abnormalities found in this study were hematology (anemia 73.71%, leucopenia 32.67%, lymphopenia 76.89%, thrombocytopenia 33.86%), kidney function (high serum creatinine levels 39.66%, high BUN levels 41.2%, hypoalbuminemia 62.6%), urine (proteinuria 68.21%, hematuria 51.79%) and liver function (high ALT levels 36.65%, high AST levels 29.86%). Infection occurred in 33.7% patients. The most common infections were pneumonia (70.65%), urinary tract infections (51.09%), and sepsis (35.87%). Conclusion: The most common clinical manifestations experienced by SLE patients are hematological disorder, kidney disorder, and arthritis. Prominent laboratory abnormalities are anemia, lymphopenia, and proteinuria. Infection is a common complication, with the most common types pneumonia, urinary tract infection, and sepsis.